Profil Pelayanan Resep dengan Obat Glibenklamid di Apotek Wilayah Nagan Raya - Razoki, Razoki; Friska Rezki Hasibuan (Yayasan Penelitian dan Inovasi Sumatera, 2025)
Background: Community pharmacies have shifted from focusing only on products to providing care centered on patients. Pharmacists now have the role of gathering patient information, giving proper counseling, and ensuring medicine labels are clear and correct. This is crucial for chronic diseases like type 2 diabetes mellitus, where drugs such as glibenclamide must be used properly to avoid risks. Objective: This study aimed to describe how pharmacies in Nagan Raya provide prescription services for glibenclamide, especially in terms of patient data collection, counseling, and labeling. Methods: A descriptive study was done using the simulated patient method. A total of 90 pharmacies were randomly chosen. The researcher acted as a patient’s family member and presented a prescription for glibenclamide. Observations were recorded right after each visit using a structured and validated checklist. Results: Of the 90 pharmacies visited, 85 (94.4%) dispensed the medicine. However, only 18.8% asked for the patient's address, and fewer than 10% asked about other key information like user identity or medication history. No pharmacy asked about symptoms, allergies, or comorbidities. For counseling, 64.7% mentioned how often to take the drug, 15.3% explained timing, and just 1.2% discussed side effects. Labels were provided in 65.9% of cases, but some were incomplete or used wrongly. Conclusion: The quality of prescription services for glibenclamide in Nagan Raya is still lacking. Important steps like patient assessment and counseling are often missed. Better training and stronger supervision are needed to improve pharmacy services and ensure patient safety